Students’ Perception of Wikipedia as an Academic Information Source - Ahmed Shafkat Sunvy; Raiyan Bin Reza (Universitas Pendidikan Ganesha, 2023)
Wikipedia has become an integral part of education in recent times. But its credibility and its ability to serve as an efficient academic resource is still a matter of concern. This study aims to evaluate Bangladeshi students’ perception of Wikipedia as an information resource. For this quantitative research, the authors used a structured questionnaires with close ended questions to collect data. A total of 336 students from several Bangladeshi institutions chosen using random sampling method were the population for this study. The collected data were analyzed using IBM SPSS Statistics 25. Kruskal Wallis and Mann-Whitney U tests were used to test the hypothesis. The study found that students regularly used Wikipedia for their academic work and classroom assignments. A majority of the students (N=296, 88.1%) deemed it appropriate to use Wikipedia in the context of university studies. This study is the first attempt in Bangladesh to investigate how frequently and why university students use Wikipedia in their academic work and whether they deem Wikipedia credible, accurate and relevant to their education. Extensive research by the authors has shown that there are many aspects of Wikipedia that make it suitable for the learning-teaching process, which makes it a fruitful topic for further study.